MERGERS AND ACQUISITIONS: AN ALTERNATIVE APPROACH - Herrera García, Beatriz (2011)
In 2010 there was a slight recovery in foreign direct investment flows. This recovery takes place after such a sharp drop in capital flows worldwide. As a result of this phenomenon of global crisis and the mergers and acquisitions, globally, have declined over the years 2008 and 2009. The main reason had to do with the effect of the global crisis that generates a decline in the ability of firms to perform such operations. However, it is considered that underthe scenario of international uncertainty mergers and acquisitions can be converted into economic growth strategies, given the possibility of buying companies at relatively low prices. The slowdown of the global market is causing a decline in the relative value of companies; however, in the Latin American market shows great dynamism, the process of mergers and acquisitionshas been to manufacturing companies, food companies and beverage, and then financial services.